Passive solar-energy air-heating wall panels - Hobday, R. A. (Cranfield University, 1987)
The development of products which enable passive solar-energy air-heating to be integrated into the heating strategies of public, commercial and industrial buildings is described. These buildings are, in general, only occupied significantly during the day; consequently the bulk of heating demand coincides with the period of solar gain. In these circumstances collected solar heat should be delivered with the minimum of delay. The design and operation of units which are capable of supplying solar heated air in this manner is outlined. These are passive, naturalcirculation air-heating collectors, also known as natural-convection air-heaters, or thermosyphoning air panels. Four methods of retrofitting such solar collectors to non-domestic buildings have been identified, one of which, the overcladding collector, has not been proposed previously. Problems associated with the successful installation and operation of these units have also been considered. The relative merits of a number of methods of testing passive solarenergy air-heating collectors have been investigated. A method of determining instantaneous collector efficiency based on the measurement of glazing temperature, inlet and outlet air temperature, ambient temperature and insolation has been developed. Three novel design proposals have been presented: i) a collector constructed with the insulation fitted outside, rather than inside, so that the metal body of the collector may provide more symmetrical heating of the air flow than the conventional arrangement, ii) an absorber which consisted of parallel ducts to increase the rate of heat transfer to the air, heating it symmetrically, (iii) a hinged air-deflector for conversion from the heating to the ventilation mode.